Secondary Hemophagocytic Lymphohistiocytosis with Severe Dengue: A Rare but Dreadful Complication - Ashwani K Sood; Saguna Pandit; Nidhi Chadha; Naresh I Jindal (Pediatric Infectious Disease)
Hemophagocytic lymphohistiocytosis (HLH) is a devastating and rare multisystemic disorder characterized by an autoimmune phenomenon leading to reactive hyperactivity of cytotoxic T cells and histiocytes mediated by cytokine storm. HLH could be primary (hereditary) or secondary (acquired). Unremittent fever, organomegaly, lymphadenopathy, and neurologic dysfunction are among the common manifestations of HLH, along with abnormal lab parameters like hyperferritinemia, hypertriglyceridemia, hypofibrinogenemia, and transaminitis. We report a case of a 16-year-old adolescent girl presenting to the emergency department with a history of high-grade fever, with partial response to antipyretics, body aches, and severe headache for 4 days. The physical examination revealed significant hepatomegaly. enzyme-linked immunosorbent assay was positive for dengue nonstructural protein 1 (NS1) antigen (Ag) assay. The patient was managed as per the World Health Organization (WHO) protocol and started improving from dengue; however, during the second week of the illness, the patient continued to have persistent fever. A repeat lab workup revealed bicytopenia with elevated ferritin levels (17891 ng/mL). Diagnosing dengue-associated HLH is challenging unless the treating team is aware of this association, as early recognition and timely institution of immunosuppressive and specific therapy for the underlying infection is associated with improved outcomes. Physicians should collaborate with pathologists and microbiologists for early diagnosis.